A Rare Combination of Left-Sided Gastroschisis and Omphalocele in a Full-Term Neonate: A Case Report - Masden, Tyler (Am J Case Rep, 2020)
Patient: Female, Newborn Final Diagnosis: Omphalocele Symptoms: Congenital abdominal wall defect Medication:— Clinical Procedure: — Specialty: Surgery OBJECTIVE: Congenital defects/diseases BACKGROUND: Left-sided gastroschisis is a rare congenital birth defect characterized by herniation of intra-abdominal organs through an abdominal wall defect to the left of the umbilicus. Approximately half of the 31 cases reported in the literature describe other associated anomalies. To the best of our knowledge, it has never been reported in association with an omphalocele. CASE REPORT: Here, we present the case of a female newborn, 37 weeks gestational age, born with a 3×6 cm omphalocele and a left-sided gastroschisis with herniation of the small bowel. Both of these anomalies were managed separately, with initial placement of a silo bag on the gastroschisis defect and application of topical agents to the omphalocele until complete epithelialization was achieved. The herniated bowel at the gastroschisis site was reduced with the aid of the silo by 96 hours and the fascia then closed primarily. A gastrostomy tube (G-tube) was placed at 16 weeks of age because of poor oral intake. Definitive closure of the omphalocele and removal of the gastrostomy tube was achieved at 13 months. Her subsequent follow-up visits in the clinic have been uneventful. CONCLUSIONS: Our case report highlights the importance of recognizing this combination of rare conditions and directing appropriate surgical care.